2013
DOI: 10.3343/alm.2013.33.4.248
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genetic Abnormalities on the Prognoses and Clinical Parameters of Patients with Multiple Myeloma

Abstract: BackgroundWe reviewed patients with multiple myeloma (MM) in order to assess the incidence of genetic abnormalities and their associations with clinical parameters, risk groups, and prognosis.MethodsA total of 130 patients with MM were enrolled. The incidences of genetic abnormalities were determined in all patients. The relationships of the genetic abnormalities and clinical parameters were investigated. In addition, a survival analysis was performed.ResultsAbnormal karyotypes were detected in 42.3% (N=55) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
25
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 27 publications
10
25
3
3
Order By: Relevance
“…It stratifies patients by their albumin and β2-microglobulin levels [13] . Regarding patients' clinical staging in the present study according to the international staging system, 7 patients (22.6%) were in stage Ι, which was nearly similar to Jekarl et al (2013) (21.5%) [4] , however it was lower than that reported in the Chinese study by Chen et al (2007) (45.8%) [3] , and Shin et al (2015) (32.4%) [13] in their recent Korean study. On the contrary, it was higher than that detected by Liu et al (2015) (10.5%) [14] whose…”
Section: Disscusionsupporting
confidence: 71%
See 3 more Smart Citations
“…It stratifies patients by their albumin and β2-microglobulin levels [13] . Regarding patients' clinical staging in the present study according to the international staging system, 7 patients (22.6%) were in stage Ι, which was nearly similar to Jekarl et al (2013) (21.5%) [4] , however it was lower than that reported in the Chinese study by Chen et al (2007) (45.8%) [3] , and Shin et al (2015) (32.4%) [13] in their recent Korean study. On the contrary, it was higher than that detected by Liu et al (2015) (10.5%) [14] whose…”
Section: Disscusionsupporting
confidence: 71%
“…Regarding stage II, 10 patients (32.3%) were detected in this study which was nearly similar to that reported by Chen et al (2007) (33.3%) [3] , while it was marginally lower than that observed by Liu et al (2015) (37.1%) [14] , Shin et al (2015) (39.7%) [13] , and Jekarl et al (2013) (43.9%) [4] . In the current study, 14 patients (45.2%) were in stage III, which was higher than that reported by Jekarl et al…”
Section: Disscusionsupporting
confidence: 64%
See 2 more Smart Citations
“…However, to date the advance of proteomics in MM research lags significantly behind the other mentioned technologies. Proteomic studies in myeloma has been largely limited to serum profiling [10][11][12][13]. The clinical applicability of the few published reports on cellular profiling of MM cells are hampered at least in part by the following: 1) the different techniques and statistical platforms used by different investigators, hence not allowing cross-validation; 2) the lack of standard procedures for sample collection, storage, and processing, hence causing background noises and lowered sensitivity of the test; and 3) limited sample numbers, hence lacking statistical power for clinical correlation analysis.…”
Section: Introductionmentioning
confidence: 99%